A Micro-Level Analysis of Physiological Responses to COVID-19: Continuous Monitoring of Pregnant Women in California - Jimah, Tamara; Kehoe, Priscilla; Borg, Holly; Pimentel, Pamela; Rahmani, Amir; Dutt, Nikil; Guo, Yuqing (Frontiers in Public Health, 2022)
Continuous monitoring of perinatal women in a descriptive case study allowed us the opportunity to examine the time during which the COVID-19 virus led to physiological changes in two low-income pregnant women. An important component of the parent study was the use of a wearable sensor device, the Oura smart ring, to monitor and record vital physiological parameters during sleep. Two women in their 2nd and 3rd trimesters were selected based on a positive COVID-19 diagnosis. Both women were tested using the polymerase chain reaction method confirming the presence of the virus during which time we were able to collect these critical data. In both cases, we observed 3-6 days of peak physiological changes in resting heart rate (RHR), resting heart rate variability (RHRV), resting respiratory rate (RR), sleep duration and stages prior to and surrounding the COVID-19 test. The pregnant woman in her 3rd trimester showed a significant increase in RHR (p=0.006) and RR (p=0.048), and a significant decrease in RHRV (p=0.027) and the deep sleep stage (p=0.029). She reported experiencing moderate symptoms and did not require hospitalization. Her delivery and baby appeared normal at 37 weeks of gestation. The participant in her 2nd trimester showed similar changes. Importantly, these changes appeared to return to pre-peak levels three days following the peak period. Common symptoms reported by both cases included loss of smell and nasal congestion. Results suggest the potential to use the evident variations in cardiorespiratory responses and sleep for real-time monitoring of disease progression during pregnancy.